Organisational love : external stakeholder perspective on organisation showing affection in B2B relationship - Mattinen, Jenni (2022)
The aim of this study is to investigate love in organisation-stakeholder relationships (OSR). While brand love research typically examines stakeholders’ love for brands and organisations, this study examines organisations’ love for stakeholders - an outside-in perspective which is under-explored in public relations and marketing research. Building on Badham’s (2020) organisation-stakeholder love framework (OSL), the aim is to explore whether stakeholders perceive an organisation’s love for them, particularly the elements of passion, intimacy, and commitment.